A microfluidic dual-well device for high-throughput single-cell capture and culture. Issue 14 (10th June 2015) - Lin, Ching-Hui; Hsiao, Yi-Hsing; Chang, Hao-Chen; Yeh, Chuan-Feng; He, Cheng-Kun; Salm, Eric M.; Chen, Chihchen; Chiu, Ing-Ming; Hsu, Chia-Hsien
Abstract : The dual-well device consists of two microwell array sets, in which the small microwells are used for single-cell capture whereas the large microwells are used for cell culture. Abstract : In vitro culture of single cells facilitates biological studies by deconvoluting complications from cell population heterogeneity. However, there is still a lack of simple yet high-throughput methods to perform single cell culture experiments. In this paper, we report the development and application of a microfluidic device with a dual-well (DW) design concept for high-yield single-cell loading (~77%) in large microwells (285 and 485 μm in diameter) which allowed for cell spreading, proliferation and differentiation. The increased single-cell loading yield is achieved by using sets of small microwells termed "capture-wells" and big microwells termed "culture-wells" according to their utilities for single-cell capture and culture, respectively. This novel device architecture allows the size of the "culture" microwells to be flexibly adjusted without affecting the single-cell loading efficiency making it useful for cell culture applications as demonstrated by our experiments of KT98 mouse neural stem cell differentiation, A549 and MDA-MB-435 cancer cell proliferation, and single-cell colony formation assay with A549 cells in this paper.